2021
DOI: 10.5937/specedreh20-30163
|View full text |Cite
|
Sign up to set email alerts
|

The impact of adapted soccer program on psychosocial behavior in adolescents with Down syndrome

Abstract: Introduction. Numerous studies have proven the significant positive impact of regular physical activity on the condition of people with intellectual disability. In practice, various adapted sports activities are increasingly used for children and adolescents with disabilities. Objectives. The current feasibility study determined the effect of soccer program on some psychosocial characteristics in adolescents with Down syndrome. Methods. 20 adolescents were recruited and randomized into two groups (the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Our main findings were that adolescents with DS, who were part of the exercise group, decreased their levels in all psychosocial variables and increase level in only one of three motoric variables following the 16-week soccer programme. These findings reinforced the idea that adapted sports programmes could improve some indicators of psychomotor and social behaviour in this target population and confirmed the results of previous studies, especially those related to soccer (Özer et al 2012;Baran et al 2013;Camacho et al 2021;Perić and Milićević-Marinković 2021).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our main findings were that adolescents with DS, who were part of the exercise group, decreased their levels in all psychosocial variables and increase level in only one of three motoric variables following the 16-week soccer programme. These findings reinforced the idea that adapted sports programmes could improve some indicators of psychomotor and social behaviour in this target population and confirmed the results of previous studies, especially those related to soccer (Özer et al 2012;Baran et al 2013;Camacho et al 2021;Perić and Milićević-Marinković 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In addition to physical activity in general, some studies have reported positive effects of specific programmes: adapted basketball (Kocić et al 2017), swimming and water activities (Yilmaz et al 2009;Suarez-Villadat et al 2020), table tennis (Chen et al 2015), karate (Perić et al 2018) and finally adapted soccer (Özer et al 2012;Baran et al 2013;Camacho et al 2021;Perić and Milićević-Marinković 2021). The aim of the current study is to determine the effects of adapted soccer programme on the motor learning and different psychosocial characteristics in adolescents with DS.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations